Determinants of Principal Performance in Madrasah: The Role of Tawhid-Based Decision Making, Leadership Behavior, and Communication Style - Nurdin, Nurdin; Ananda, Rusydi; Syukri, Makmur (STAI Publisistik Thawalib Jakarta, 2026)
This study examines the limitations in the integration of tawhid-based decision making, leadership behavior, and communication style in improving the performance of madrasah principals, which has so far been analyzed partially and has not been comprehensively addressed. The study aims to empirically analyze the partial and simultaneous effects of tawhid-based decision making, leadership behavior, and communication style on the performance of principals of State Islamic Senior High Schools (MAN) in Medan. A quantitative ex post facto correlational study was conducted at MAN 1, MAN 2, and MAN 3 Medan with a sample of 60 respondents. Data were collected using valid and reliable questionnaires and analyzed using multiple linear regression. The results show that tawhid-based decision-making has a positive and significant effect on madrasah principal performance, with a coefficient of 0.365 and a significance value of 0.005. In contrast, leadership behavior is not significant, with a coefficient of 0.022 and a significance value of 0.872. Communication style is the most dominant variable, with a coefficient of 0.479 and a significance value of 0.000. Simultaneously, the three variables have a significant effect, with an F value of 19.583 and an R² of 0.512. The performance of madrasah principals is significantly influenced by tawhid-based decision-making and communication style, with communication being the dominant factor. This study strengthens Islamic leadership theory and provides practical implications for improving performance through the integration of spiritual values and effective communication.